2021
DOI: 10.1186/s13018-021-02395-5
|View full text |Cite
|
Sign up to set email alerts
|

Factors related to large bone defects of bipolar lesions and a high number of instability episodes with anterior glenohumeral instability

Abstract: Background Significant bone defects are associated with poor clinical results after surgical stabilization in cases of glenohumeral instability. Although multiple factors are thought to adversely affect enlargement of bipolar bone loss and increased shoulder instability, these factors have not been sufficiently evaluated. The purpose of this study was to identify the factors related to greater bone defects and a higher number of instability episodes in patients with glenohumeral instability. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…27,35,39 Despite having a lower regression coefficient than the native glenoid depth, the glenoid depth of the affected shoulder was also shown to be an independent indicator of HSL depth, suggesting that the postinjury condition of the glenoid concavity may have some bearing on HSL depth. Moreover, when the previously disregarded feature, native glenoid depth, was included in the regression model, the glenoid bone loss, which has been shown to greatly influence the HSL size in previous research, 27,28,36,40 did not exhibit any significant correlations with HSL depth, width, or volume. This showed that the morphological association between bipolar bone loss might be misestimated when considering only 2D glenoid characteristics without the concavity depth.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…27,35,39 Despite having a lower regression coefficient than the native glenoid depth, the glenoid depth of the affected shoulder was also shown to be an independent indicator of HSL depth, suggesting that the postinjury condition of the glenoid concavity may have some bearing on HSL depth. Moreover, when the previously disregarded feature, native glenoid depth, was included in the regression model, the glenoid bone loss, which has been shown to greatly influence the HSL size in previous research, 27,28,36,40 did not exhibit any significant correlations with HSL depth, width, or volume. This showed that the morphological association between bipolar bone loss might be misestimated when considering only 2D glenoid characteristics without the concavity depth.…”
Section: Discussionmentioning
confidence: 98%
“…HSL morphology significantly affects the clinical manifestations, treatment strategies, and prognosis for patients with anterior shoulder instability. 8,16,27 In terms of the HSL size, a deep and wide HSL commonly leads to frequent frank dislocations that necessitate manual reduction, 27,56 and the preferred surgical approach for these cases might switch from the routinely used remplissage procedure to osteochondral allograft transplant due to the increased need for biomechanical stability. 15,46,58 In terms of the HSL location, a more medial HSL indicates a larger Hill-Sachs interval according to the glenoid track concept, 2,9 which would increase risk of engagement and recurrent instability after isolated Bankart repair.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is well known that bone loss in the glenoid and humeral head greatly influences shoulder instability [ 25 - 29 ]. In our study, based on radiographs, we did not observe any significant differences between first-time and recurrent group patients with regard to bone loss.…”
Section: Discussionmentioning
confidence: 99%